Changes in 24‐h Movement Behaviors During Relationship and Parenthood Transitions: A Compositional Data Analysis - Suorsa, Kristin; Lindstedt, Milja; Rasmussen, Charlotte Lund; Leskinen, Tuija; Pasanen, Jesse; Rovio, Suvi; Heinonen, Olli J.; Viikari, Jorma; Rönnemaa, Tapani; Niinikoski, Harri; Raitakari, Olli; Stenholm, Sari; et al. (Wiley, 2025)
There is scarcity of studies using device-based measures to examine how relationship and parenthood transitions modify 24-h movement behaviors. This study examined how the composition of 24-h movement behaviors changes during these life transitions. Young adults (n = 170, mean age 25.6 years, SD 0.6) from the Special Turku Coronary Risk Factor Intervention Project (STRIP) wore wrist-worn accelerometers for 1 week and completed questionnaire at ages 26 and 31 years. Participants were categorized by relationship status into single (16%), those transitioning from single to partnered (31%), partnered (47%), and separated (7%), and by parenthood status into non-parents (73%), new parents (19%), and parents (8%). Changes in daily movement behaviors, including sleep, sedentary behavior (SED), light physical activity (LPA), and moderate-to-vigorous physical activity (MVPA), were examined using compositional linear mixed models. In general, LPA and MVPA decreased relative to sleep and SED (p = 0.007). Differences emerged between LPA and MVPA in relationship and parenthood groups (p for group × time interaction 0.008 and 0.001). Those transitioning to partnership decreased MVPA by 17 min/day, while partnered and separated individuals showed no notable MVPA change but decreased LPA by 14 and 43 min/day. Single individuals and non-parents decreased LPA and MVPA in similar proportions. New parents decreased MVPA by 20 min/day, while parents increased it by 19 min/day. Becoming first-time parent and starting relationship was associated with decline of MVPA. Our results suggest the importance of considering these life transitions and providing guidance for maintaining physical activity despite changes in life situations.